A Structured Approach Using the Systematic Review Data Repository (SRDR): Building the Evidence for Oral Health Interventions in the Population With Intellectual and Developmental Disability. (April 2017) - Bonardi, Alexandra; Clifford, Christine J.; Hadar, Nira
Background: This review describes the methods used for a systematic review of oral health intervention literature in a target population (people with intellectual and developmental disability (I/DD)), which spans a broad range of interventions and study types, conducted with specialized software. Objective: The aim of this article is to demonstrate the review strategy, using the free, online systematic review data repository (SRDR) tool, for oral health interventions aimed at reducing disparities between people with I/DD and the general population. Research Design: Researchers used online title/abstract review (Abstrackr) and data extraction (SRDR) tools to structure the literature review and data extraction. A practicing clinician and an expert methodologist completed the quality review for each study. The data extraction team reported on the experience of using and customizing the SRDR. Results: Using the SRDR, the team developed four extraction templates for eight key questions and completed extraction on 125 articles. Conclusions: This report discusses the advantages and disadvantages of using an electronic tool, such as the SRDR, in completing a systematic review in an area of growing research. This review provides valuable insight for researchers who are considering the use of the SRDR.